Pengembangan Sistem Manajemen Tengkulak Kopi Given Berbasis Web - Muhammad Aulia Rahman; Fajar Pradana; Edy Santoso (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
One type of beverage that comes from plants is coffee, coffee is made from processed coffee plant crops in the form of seeds. Coffee belongs to the Rubiaceae family with the genus Coffea. Coffee can also be included in the class of psychostimulant drinks which can temporarily relieve drowsiness, reduce fatigue, and increase energy as a physiological effect. The increase in the coffee industry in Indonesia is marked by the increase in consumption of processed coffee products with a percentage of up to more than seven percent in 2016 and continues to increase every year. Given coffee middlemen, as one of the coffee industry players run by the munte family, which began in 2000. Given's coffee middleman business process, which starts with purchasing coffee beans from the harvest that must be done on market days, from Thursday to Saturday every week is considered not effective to meet the needs of three tons of processed coffee stock every month. Furthermore, the sales or promotion process which is still by word of mouth is considered outdated and often reduces profits because there are often brokers who promote products to buyers and ask for profit sharing for their promotions. Based on these problems, a system is made to simplify the process of buying and selling coffee beans at given coffee wholesalers. The system development stage includes the stages of needs analysis, implementation, and testing. In the analysis step, there are 32 functional requirements and one non-functional requirement. The implementation stages use the PHP programming language on the CodeIgniter framework and MySQL in the database section. Then the testing step consists of several tests such as functional and non-functional testing. Functional testing consists of unit testing that successfully runs the test path based on 3 test cases, integration testing on the method obtains valid status and validation testing obtains 100% validity from 49 test cases. Non-functional testing using usability testing obtained system results that were acceptable to users with a final score of 73.25.